Increased C-reactive protein concentrations were associated with suicidal behavior in patients with depressive disorders: a meta-analysis. (October 2020) - Chen, Xiang; Pu, Juncai; Liu, Yiyun; Tian, Lu; Chen, Yue; Gui, Siwen; Xu, Shaohua; Song, Xuemian; Xie, Peng
Highlights: A meta-analysis of evaluating differences of CRP concentrations in suicidal PDDs. Peripheral CRP levels were significantly increased in patients with suicidal PDDs. The results support that inflammatory processes may be involved in suicidal behavior. Abstract: Suicide is devastating with a high incidence in patients with depressive disorder (PDDs). Although some studies have explored underlying associations between C-reactive protein (CRP) levels and suicidal behavior in PDDs, consistent results have not been reached. Therefore, the aim of this meta-analysis was to explore the differences of peripheral blood CRP concentrations between suicidal and non-suicidal PDDs, and between suicidal PDDs and healthy controls (HCs). To this end, PubMed, Embase, and Web of science were searched for eligible studies, and pooled effect sizes from eligible studies were calculated by random-effect models. Furthermore, sensitivity and meta-regression analyses were performed to explain the causes of heterogeneity. Eventually, 7 studies with 2, 108 participants were included. Our statistical results suggested that the concentrations of peripheral CRP may be significantly increased for suicidal PDDs, both compared with non-suicidal PDDs and HCs, respectively. The differences of detection methods may be linked with the sources of heterogeneity. In short, our findings showed both compared with non-suicidal PDDs and HCs, peripheral blood CRP levels may be significantly increased in suicidal PDDs, while more studies with large sample sizes are needed to validate our findings.